ABS-CBN VS CNN Philippines an analysis of the documentaries made by both networks on the Marawi Siege - Fernandez, Mary Therese Chua 1997- (2018)
"This thesis is a textual analysis of the documentaries produced by both ABS-CBN and CNN Philippines in their coverage of the Marawi siege. In particular, this study analyzes ABS-CBN's :Di Ka Pasisiil (Never Be Oppressed)" and CNN Philippines' "Inside Marawi: Documentary Special". The author looks into the labels and narrative of both documentaries to answer the research question, "How did the documentaries label and present the Daulah Iskamiyah Wilayatul Mashriq?" The author also compared the findings for both documentaries. Furthermore, this study also looks into the accuracy of information both documentaries presented and whether there were violations to the Broadcast Code of the Kapisanan ng mga Brodkaster ng Pilipinas (KBP). The findings state that both documentaries have wrongly labeled the Daulah Islamiyah Wilayatul Mashriq and at the same time also have inaccuracy in the information presented. Furthermore, there were also violations to the KBP Broadcast Code from both documentaries."